Co-creation services boosting health technology potential – the case of Turku Finland - Lahtiranta Janne; Reunanen Tero; Kontio Elina (United States, 2025)
Especially in health technology, developing an idea into a marketable solution, is a long and winding role. More so in the case of medical devices, that play an essential role in healthcare delivery of today. These devices are solutions that are intended for medical use in “homes and hospitals”. Regulating their development ensures the devices are safe to use, and available to the end-users on global markets. As the regulatory framework expands beyond development to sales, regulatory compliance is of paramount importance for every organization working in the field. To enable the development of medical devices, and other solutions of health technology, we have created a platform called “Terttu” (engl. “Bunch” as in “bunch of grapes”) that brokers and facilitates regional co-creation services to companies in need of them. In our previous article, we created a theoretical framework for the platform. In this one, we take a deep dive into the actual results of our development.In the core, the Terttu service was developed using Service Design as the over-arching design principle. The service is an electronic platform used for matching the end-user (company) co-creation needs with the services available in the regional. “Under the hood”, the service is also used for combining different co-creation services together, in the case that a single service can’t meet the needs of the end-user. And, when there is a match between the need and the co-creation service(s), Terttu provides a way for advancing a contact into an actual agreement between the involved parties, and using a completed co-creation project as a reference in promoting the service.The actual work in developing the platform started with focus group interviews. In these interviews, the end-users’ (9 companies) needs, wishes, and ideas for the Terttu service were investigated. As the services is intended to be used in the healthcare sector, the companies were selected accordingly. In the interviews, the end-users were walked through the intended process of initiating co-creation from their perspective, and after that the users were given the floor; how the process worked, how it should have worked, and what would be an ideal process. On the basis of these interviews, an ideal version of the Terttu service was drafted, and presented to the co-creation service providers. These in turn, had an option to add their insights into the drafted version, that would eventually steer the development of the Terttu service.This collaborative work with the end-users and the service providers resulted in a shared vision of a service – the way it should look, and the way the promises to the end-users should be redeemed. However, it turned out that this was just the icing on the cake. There were still practical, and fundamental, issues to be addressed before the vision would could be done true. The development work brought to light a) problems associated with the ownership and management of the Terttu service, b) ambiguities in the way the service promise was initially formulated, and c) challenges in the marketing and pricing. All these would need hard work and making compromises from all service provider organizations. Future research aspects and practical recommendations will also be issued in the paper.
Creativity, Innovation and Entrepreneurship: Proceedings of the 13th AHFE International Conference on Creativity, Innovation and Entrepreneurship, New York July 24-28 2022